2024
DOI: 10.1002/ange.202405287
|View full text |Cite
|
Sign up to set email alerts
|

ON–OFF Control of Marangoni Self‐propulsion via A Supra‐amphiphile Fuel and Switch

Guiqiang Zhu,
Shu Zhang,
Guoxin Lu
et al.

Abstract: Marangoni self‐propulsion refers to motions of liquid or solids driven by a surface tension gradient, and has applications in soft robots/devices, cargo delivery, self‐assembly etc. However, two problems remain to be addressed for motion control (e.g., ON‐OFF) with conventional surfactants as Marangoni fuel: (1) limited motion lifetime due to saturated interfacial adsorption of surfactants; (2) in‐ situ motion stop is difficult once Marangoni flows are triggered. Instead of covalent surfactants, supra‐amphiphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Ces et al reported that v / r follows as (similar equations are shown in refs and in ref ) v r = C p x γ C p 1 2 η o + 3 η i where C p is the PEG concentration outside the droplet, x is the position of the droplet center of gravity, γ is the interfacial tension between the dextran-rich phase and the PEG rich phase, and η o (or η i ) is the solution viscosity outside (or inside) the droplet. In our experimental system, Reynolds number Re is estimated to be ≪1 (for example, Re = ρ vr /η o ∼ 10 –6 by using ρ = 1.01 × 10 3 kg/m 3 , v = 1 μm/s, r = 10 μm, η o = 10 mPa s) so that the contributions of Marangoni convection and drag forces to the velocity should balance immediately.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Ces et al reported that v / r follows as (similar equations are shown in refs and in ref ) v r = C p x γ C p 1 2 η o + 3 η i where C p is the PEG concentration outside the droplet, x is the position of the droplet center of gravity, γ is the interfacial tension between the dextran-rich phase and the PEG rich phase, and η o (or η i ) is the solution viscosity outside (or inside) the droplet. In our experimental system, Reynolds number Re is estimated to be ≪1 (for example, Re = ρ vr /η o ∼ 10 –6 by using ρ = 1.01 × 10 3 kg/m 3 , v = 1 μm/s, r = 10 μm, η o = 10 mPa s) so that the contributions of Marangoni convection and drag forces to the velocity should balance immediately.…”
Section: Resultsmentioning
confidence: 54%
“…This alternation of droplet motile velocity via DNA conformational change will contribute to applied research using droplets as soft robots. 44 In addition, combining this system with Marangoni convections driven by chemical reactions, 45−47 concentration gradients of surfactants, 48,49 and local heating, 50,51 more complex and longterm movements of motile droplets will be expected. Incorporation of various biopolymers should result in shearinduced segregation 52 and also the alignments of stiff polymers such as collagen fibrils by the flow.…”
Section: Discussionmentioning
confidence: 99%